MENINGKATKAN KETERAMPILAN SISWA DAN KUALITAS BELAJAR FISIKA PADA MATERI GETARAN DENGAN MEMADUKAN OBSERVASI BERBASIS EKSPERIMEN DI LABORATORIUM SMAN 1 SIGLI - Darwati darwati (JURNAL FISIKA EDUKASI, 2015)
The Research objectives of this class is to find out the influence of learning by improving skills and the quality by combining the observation-based on experiments in the laboratory, besides the students can develop skills, science process skills, solve problems and improve the interaction of students in the teaching and learning process. This research uses experimental methods consist of 2 cycles. Each cycle consists of 4 components such as; planning, implementation measures, observation and reflection. The subject of this research is the grade XI at SMAN 1 Sigli. The research sample was obtained from class XI IPA 5 with 30 students. I the techniques of data collection of tests and observations or observations made objectively against aspects which will be observed in the form of data and information. Data collection tools in the form of a question and observation instrument of sheet. Performance indicators expected results enhanced learning occurred reached 75% for study result. Percentage of class action research on cycle I gained 56,67%, while on cycle II student learning increased to 83,33% for study result.